IDEOLOGICAL SETS OF POLITICAL ATTITUDES IN LITHUANIAN SOCIETY - Petronytė, Ieva (Politologija, 2013)
Everyday public discourse and empirical researches show that the ideological thinking among the major part of Lithuanian society is practically non-existent (political attitudes are found to be incoherent, and opinions are seemingly self-contradictory). Such unpopularity of ideological thinking makes it difficult to predict the political outlooks and behavior of the public and potentially challenges the foundations of the representative democracy. However, conclusions on the broader political thinking inconsistency in society would be hasty without evaluating the existence of alternative coherent belief systems or systems of political attitudes. In other words, the methodological perspective is worth to be changed: from searching ideological thinking along presupposed strict ideological lines as suggested by the classical political thought, to looking for the possible other consistencies in the same field, other sets of the same political attitudes. In this article, primary results of such research, obtained after applying the Q-sort methodology, are presented, and three shared social perspectives, which operate as certain political ideologies among Lithuanian public, are discussed. The first one, conditionally named free self-expression discourse, centre on the extensive advocacy of free, equally for everybody accessible self-expression idea and a strong opposition to any restrictions of personal freedom and choice. Though economic issues do not play a key role in this perspective, along the ideas of free market competition the priority lies on some “minimum” of care, which the state ought to ensure for its population. The second perspective is based on the perception of the current situation in the state and society as chaotic, flawed, and reveals longing for the “order” which mainly means a high priority given to one strong leader. In this shared social perspective, moral and economic issues are (at best) of secondary importance while Soviet times and current Russia are seen positively through a pragmatic and even a nostalgic prism. Finally, the third perspective, which could be called the traditional morality discourse, cherish the so-called traditional values such as respect of life, family, religion, ethnic identity, and condemns the Soviet regime in which these values were suppressed. These three shared social perspectives could be respectively linked with the ideologies of social liberalism, authoritarianism, and conservatism. However, emphasizing the authenticity of these perspectives, the interconnections should be deliberated and not too much binding. Most important, these perspectives could be regarded as an evidence of coherent political thinking in Lithuanian society – internally coherent political belief systems are found, and they are shared by society members.